2021
DOI: 10.1121/10.0008930
|View full text |Cite
|
Sign up to set email alerts
|

How pronunciation distance impacts word recognition in children and adults

Abstract: Although unfamiliar accents can pose word identification challenges for children and adults, few studies have directly compared perception of multiple nonnative and regional accents or quantified how the extent of deviation from the ambient accent impacts word identification accuracy across development. To address these gaps, 5- to 7-year-old children's and adults' word identification accuracy with native (Midland American, British, Scottish), nonnative (German-, Mandarin-, Japanese-accented English) and bilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…While tentative, another possible explanation for greater alignment toward Indian English is phonetic distance. Recent work has shown a greater number of phonetic "edits" from American English varieties to Hindi-English than to RP (Bent et al, 2021). In our stimuli, many items contained a contrast in VOT in addition to a contrast in vowel length or quality, meaning that there was more space for US speakers to converge toward IN voices than RP voices.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…While tentative, another possible explanation for greater alignment toward Indian English is phonetic distance. Recent work has shown a greater number of phonetic "edits" from American English varieties to Hindi-English than to RP (Bent et al, 2021). In our stimuli, many items contained a contrast in VOT in addition to a contrast in vowel length or quality, meaning that there was more space for US speakers to converge toward IN voices than RP voices.…”
Section: Discussionmentioning
confidence: 96%
“…Both RP and IN English differ from US English in vowel quality and vowel length, and IN English additionally differs from US English in voice-onset time (VOT) of word-initial stops (Awan and Stine, 2011). The target words selected for this study were chosen to emphasize the phonetic distance between US to another US speaker (no change), US to RP (small change), and US to IN English (larger change) (Bent et al, 2021). Relative to US English, the stimuli differ in either vowel length or quality in RP and/or IN English, and in VOT in IN English (Wells, 1982;Schmitt, 2007;Awan and Stine, 2011).…”
Section: Current Studymentioning
confidence: 99%
“…used Levenshtein distance to measure such mismatches, revealing that children may face greater difficulties identifying words in an unfamiliar L1 regional accent than a L2 accent. These effects of pronunciation distance have been replicated and extended to other L1 and L2 varieties (Bent et al, 2021;Hanulíková, 2021), challenging the widespread view that L1 speech is generally more intelligible, cognitively less effortful, and socially more preferred than L2 speech. Moreover, Weatherhead et al (2019) underscore the role of prosodic patterns that can affect preference judgments.…”
Section: Discussionmentioning
confidence: 96%
“…An alternative explanation pertains to the acoustic and perceptual cues of the accents themselves. Several studies have demonstrated that factors such as familiarity, listening effort, and pronunciation distance can influence how individuals, including children, respond to L2 accents and regional varieties (Van Engen and Peelle, 2014;Bent, 2018;Hanulíková, 2019Hanulíková, , 2021Weatherhead et al, 2019;Bent et al, 2021). Listening effort is associated with varying processing load for different degrees of acoustic mismatch between speech produced by a speaker and a listener's variety (Van Engen and Peelle, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Given that the participants were we trained on the form and meaning of distinct words, perhaps they were approximating the word shape and producing it as such, according to it being phonologically closer to the target than to the other words. Further research could code the participant's accuracy in word productions according to the level at which they conform to the target, relative to the other target items using an Levenshtein algorithm adaptation (e.g., Bent et al, 2021;Levenshtein, 1966).…”
Section: Rq4 What Is the Effect Of Production Versus Comprehension Pr...mentioning
confidence: 99%